Determination of Aflatoxins in Medicinal Plants by High-Performance Liquid Chromatography-Tandem Mass Spectrometry - Nadeem Ahmad Siddique; Mohd Mujeeb; Sayeed Ahmad; Bibhu P. Panda; Mohd Makhmoor (Frontiers Media S.A., 2013)
Purpose. The intention of the proposed work is to study the presence of the aflatoxins B1, B2, G1 and G2 in medicinal plants, namely Mucuna pruriens, Delphinium denudatum and Portulaca oleraceae. Methodology. The aflatoxins were extracted, purified by immunoaffinity column chromatography and analysed by high-performance liquid chromatography-tandem quadrupole mass spectrometry with electrospray ionisation (HPLC-MS/MS). Fungal count was carried out in PDA media. Results. A good linear relationship was found for AFB1, AFB2, AFG1 and AFG2 at 1-10 ppb (r>0.9995). The analyte accuracy under three different spiking levels was 86.7-108.1 %, with low per cent relative standard deviations in each case. The aflatoxins can be separated within 5 to7 min using an Agilent XDB C18-column. We found that AFB1 and AFB2 were in trace amounts below the detection limit in M. pruriens whilst they were not detected in D. denudatum. P. oleraceae was found to be contaminated with AFB1 and AFB2. AFG1 and AFG2 were not detected in M. pruriens, P. oleraceae and were below the detection limit in D. denudatum. This was consistent with very low numbers of fungal colonies observed after 6 hr of incubation. Conclusion. The analytical method developed is simple, precise, accurate, economical and can be effectively used to determine the aflatoxins in medicinal plants and therefore to control the quality of products. The aflatoxin levels in the plant extracts examined were related to the minimal fungal load in the medicinal plants examined. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.